2018
DOI: 10.3390/rs10071056
|View full text |Cite
|
Sign up to set email alerts
|

Constrained Spectral Clustering of Individual Trees in Dense Forest Using Terrestrial Laser Scanning Data

Abstract: Abstract:The present study introduces an advanced method for 3D segmentation of terrestrial laser scanning data into single tree clusters. It intentionally tackled difficult forest situations with dense and structured tree formations, which inventory practitioners are often faced with. The strongly interlocking tree crowns of different sizes and in different layers characterized the test conditions of close to nature forest plots. Volumetric 3D images of the plots were derived from the original point cloud dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…Multiple studies have focused on the detection of biophysical parameters at both stand and individual scale, with major findings. Heinzel and Huber [16] reached close to 100% identification of stems position by focusing on close range segmentation; similar results are reiterated in several other papers [17] [14]. With similarly good results, studies on biophysical parameters estimation covered both diameter [18] [19][20] and heights evaluation [21] [22].…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…Multiple studies have focused on the detection of biophysical parameters at both stand and individual scale, with major findings. Heinzel and Huber [16] reached close to 100% identification of stems position by focusing on close range segmentation; similar results are reiterated in several other papers [17] [14]. With similarly good results, studies on biophysical parameters estimation covered both diameter [18] [19][20] and heights evaluation [21] [22].…”
Section: Introductionsupporting
confidence: 69%
“…The increase in the proportion of identified stems between single and multiple scans (10%) observed by Xi et al- [15] was confirmed but with higher values (16 to 29%). Literature provide overall detection percentages to exceed 97% [16,17], with a slight decrease for smaller diameters. Although depended on the structure and number of scans [24], the~10% decrease is similar to our results.…”
Section: Discussionmentioning
confidence: 99%
“…For multiple scan mode, the literature describes various scanner location patterns. In principle, the following setup patterns are distinguished: (i) the scanner positions are located at the edges of the sample plot [12,[42][43][44][45][46], (ii) the scanner positions are outside the sample plot [13,26,46,47], or (iii) one scanner position is in the center and the rest are more or less evenly distributed around it [6,39,46,[48][49][50][51][52][53][54]. Abegg et al [46] showed, in a comprehensive simulation study on the impact of scanner location on occlusion, that an intuitive distribution of scanner positions within the sample point with similar distances between the positions and edges of the sample plot ensures the best overall visibility of the stand.…”
Section: Introductionmentioning
confidence: 99%
“…Major findings of selected recent studies are described as follows. Heinzel and Huber [53] were able to detect 97.4% of tree positions with a diameter at breast height (dbh) greater or equal to 12 cm with five scanner positions on plots with 7.98 m radius. Further, 97.3% of tree positions were detected for dbhs greater or equal to 36 cm on plots with a 12.62 m radius.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of these limitations, most tree detection algorithms have been applied and tested on similar forest types with little exploration of how the algorithms generalize to other natural settings. Therefore, despite the intense work in airborne tree detection over the last decade (Coomes et al, 2017; Heinzel and Huber, 2018; Jakubowski et al, 2013; Li et al, 2012; Williams et al, 2019), there remains no clear consensus on best practices (Aubry-Kientz et al, 2019).…”
Section: Introductionmentioning
confidence: 99%